Graduate views on access to higher education: is it really a case of pulling up the ladder? - Webb, Rob; Watson, Duncan; Cook, Steve; Arico, Fabio (Taylor & Francis, 2015)
Using as a starting point in the recent work of Mountford-Zimdars et al., the authors analyse attitudes towards expanding higher education (HE) opportunities in the UK. The authors propose that the approach of Mountford-Zimdars et al. is flawed not only in its adoption of a multivariate logistic regression but also in its interpretation of results. The authors make a number of adaptations, chief among them being the use of an ordered probit approach and the addition of a time dimension to test for changes in attitudes between 2000 and 2010. The authors find that attitudes towards HE expansion have intensified during the decade 2000–2010, but the authors uncover no evidence that this is due to graduates wanting to ‘pull up the ladder’, as suggested by Mountford-Zimdars et al. The authors argue that evidence of a widespread desire to reduce access to HE can most likely be explained by social congestion theory, internal institutional disaffection and rising tuition fees.